2019
DOI: 10.25248/reas.e1500.2019
|View full text |Cite
|
Sign up to set email alerts
|

Perfil sociodemográfico, situação de saúde e práticas de autocuidado dos idosos com Doença Crônica Não Transmissível em um município Amazônico

Abstract: Objetivo: Caracterizar o perfil sociodemográfico, situação de saúde e as práticas de autocuidado em idosos cadastrados na rede básica de saúde do município de Coari, Estado do Amazonas. Métodos: Estudo exploratório, descritivo e transversal com abordagem quantitativa, com população de 340 idosos. A coleta de dados ocorreu no mês de janeiro a junho de 2015, por meio de formulário sociodemográfico, situação de saúde e práticas de autocuidado. Resultados: Predominância do sexo feminino (59,0%), faixa etária de 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In the national and international scientific literature, there is little research that associates self-care with varied health practices in community older adults. The studies found related the theme to some chronic noncommunicable disease (NCD) (6) as diabetes mellitus (7)(8)(9) and hypertension (10) . It is also noteworthy the knowledge gap in research that focuses on self-care in health based on nursing theories.…”
Section: Introductionmentioning
confidence: 99%
“…In the national and international scientific literature, there is little research that associates self-care with varied health practices in community older adults. The studies found related the theme to some chronic noncommunicable disease (NCD) (6) as diabetes mellitus (7)(8)(9) and hypertension (10) . It is also noteworthy the knowledge gap in research that focuses on self-care in health based on nursing theories.…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura científica nacional e internacional, são escassas as pesquisas que associam o autocuidado com práticas de saúde variadas em idosos da comunidade. Os estudos encontrados relacionaram o tema com alguma doença crônica não transmissível (DCNT) (6) , como diabetes mellitus (7)(8)(9) e hipertensão arterial sistêmica (10) . Destaca-se, ainda, a lacuna de conhecimento em pesquisas que enfocam o autocuidado em saúde pautado nas teorias de enfermagem.…”
Section: Introductionunclassified